2023
DOI: 10.1371/journal.pone.0285571
|View full text |Cite
|
Sign up to set email alerts
|

The association between HIV diagnosis disclosure and adherence to anti-retroviral therapy among adolescents living with HIV in Sub-Saharan Africa: A systematic review and meta-analysis

Abstract: Introduction Nine in ten of the world’s 1.74 million adolescents living with human immunodeficiency virus (ALHIV) live in Sub-Saharan Africa. Suboptimal adherence to antiretroviral therapy (ART) and poor viral suppression are important problems among adolescents. To guide intervention efforts in this regard, this review presented pooled estimates on the prevalence of adherence and how it is affected by disclosure of HIV status among ALHIV in Sub-Saharan Africa. Methods A comprehensive search in major databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…In Kenya, perinatal HIV disclosure rates have been documented as low as 36.6% among AYLHIV [28]. Data from Kenya and other sub-Saharan African countries suggest that disclosure of HIV status to perinatally-infected AYLHIV is associated with improved treatment adherence and immunological status [10,29,30]. Similarly, in our study, disclosure was described to help AYLHIV understand the diagnosis and need for treatment.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In Kenya, perinatal HIV disclosure rates have been documented as low as 36.6% among AYLHIV [28]. Data from Kenya and other sub-Saharan African countries suggest that disclosure of HIV status to perinatally-infected AYLHIV is associated with improved treatment adherence and immunological status [10,29,30]. Similarly, in our study, disclosure was described to help AYLHIV understand the diagnosis and need for treatment.…”
Section: Discussionsupporting
confidence: 65%
“…These barriers included stigma, poverty, fear of disclosure, mental health challenges, and limited social support, including non-supportive behavior by healthcare workers [9]. The challenges and complexities AYLHIV experience concerning disclosure of HIV status, stigma, and treatment management are well documented in the literature alongside the implications these experiences have on AYLHIV long-term engagement and retention in care [10]. In school settings, in particular, stigma perpetrated by teachers and peers has been described in published studies from Kenya, where boarding schools are common and many AYLHIV chose not to disclose their HIV status and treatment to the educators and school staff [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This was corroborated by a study conducted by Kitetele et al (2023), who found that APHIV that were fully disclosed felt like their HIV-negative peers when they had to make informed decisions about sexual relationships [16]. Furthermore, different authors acknowledge the positive association between full disclosure and better adherence to ART, participation in less risky lifestyles, and improved mental health [1,7,19,26].…”
Section: Hiv-positive Status Disclosure Processmentioning
confidence: 92%
“…However, these adolescents were not disclosed during diagnosis due to their young age and the nature of acquisition. Their status was only disclosed later in life, leading to adverse health outcomes and other problems [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of one’s HIV status was a factor in ART adherence among adolescents. 12 , 13 A study among eight SSA countries revealed stigma, ART side effects, lack of resistance and forgetfulness as barriers to ART adherence. 14 The findings of a study conducted in Yaounde, Cameroon proved that poor ART adherence is associated with the presence of depressed mood, virologic failure, disease progression and treatment failure.…”
Section: Introductionmentioning
confidence: 99%